2008
DOI: 10.1080/87565640701884220
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Caretaker Report and Hands-On Neurodevelopmental Screening in High-Risk Infants

Abstract: Caretaker report in developmental screening of high-risk infants has not been investigated adequately. We compare a caretaker-completed neurodevelopmental prescreening questionnaire (NPQ) to a hands-on screener (Bayley Infant Neurodevelopmental Screener; BINS) and attempt to identify factors that influence agreement in a high-risk sample. From 1,436 infants drawn from 5 centers, 471 were prospectively evaluated at 6-months corrected age, 376 at 12-months, and 244 at 24-months. Fifty-five percent were male; 28%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Sensitivity and specificity values, as well as positive and negative predictive values for the motor assessment battery, the Perinatal Follow-up Clinic protocol and the DCDQ, using the Movement ABC as the reference standard were derived and the percent agreement among these protocols was investigated. The Movement ABC is a "reference standard" and not a "gold standard"; therefore, sensitivity was considered co-positivity, and specificity, co-negativity (Aylward & Verhulst, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity and specificity values, as well as positive and negative predictive values for the motor assessment battery, the Perinatal Follow-up Clinic protocol and the DCDQ, using the Movement ABC as the reference standard were derived and the percent agreement among these protocols was investigated. The Movement ABC is a "reference standard" and not a "gold standard"; therefore, sensitivity was considered co-positivity, and specificity, co-negativity (Aylward & Verhulst, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A concurrent validity for the BINS and Bayley Scales of Infant Development II (BSID-II) yielded Pearson correlation coefficients (r) that ranged from 0.43 to 0.82 for the Mental Developmental Index and 0.39 to 0.58 for the Psychomotor Developmental Index (Aylward, 2010). Studies of predictive validity showed that an early classification of an infant in the high-risk category was a strong indicator of future developmental problems (Aylward, 1995, 1998; Aylward & Verhulst, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Camp 12 underscores the issue of spectrum bias where better or worse identification depends on base rates of problems. Diamond and Squires 13 For example, in a high-risk follow-up population an average 76% agreement was found between a hands-on screening instrument and a parent-completed questionnaire 11 accompanied by video examples. The actual screening risk status of the infant (low, medium, high) was the variable most predictive of agreement at 6 and 12 months; at 24 months, race (a marker for socioeconomic status) was predictive.…”
Section: Is Caretaker Report Sufficient For Developmental Screening?mentioning
confidence: 97%
“…10 Without doubt, caretaker completed questionnaires are attractive because of wide applicability, low cost, and decreased time demands. However, although these questionnaires have been favorably compared with other reference standards, 9,11 little is known as to how these instruments are affected by child-related or environmental factors (aside from parent reading level).…”
Section: Is Caretaker Report Sufficient For Developmental Screening?mentioning
confidence: 98%